2014
DOI: 10.1155/2014/901901
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Perioperative Corneal Abrasions

Abstract: Purpose. To evaluate perioperative risk factors for corneal abrasion (CA) and to determine current care for perioperative CA in a tertiary care setting. Methods. Hospital-based, cross-sectional study. In Operating Room and Post-Anesthesia Care Units patients, a comparison of cases and controls was evaluated to elucidate risk factors, time to treatment, and most common treatments prescribed for corneal abrasions. Results. 86 cases of corneal abrasion and 89 controls were identified from the 78,542 surgical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 16 publications
4
46
0
Order By: Relevance
“…Studies did not suggest a routine eye patch for corneal abrasions, because it does not have any effect on healing time and pain (10). It has also been indicated that smaller abrasions, as in CFB trauma, could be treated only with antibiotic ointments (11). Following CFB removal, all patients in the current study were prescribed ocular antibiotic drops without eye patching, and then patients were re-assessed two days after the procedure.…”
Section: Discussionmentioning
confidence: 94%
“…Studies did not suggest a routine eye patch for corneal abrasions, because it does not have any effect on healing time and pain (10). It has also been indicated that smaller abrasions, as in CFB trauma, could be treated only with antibiotic ointments (11). Following CFB removal, all patients in the current study were prescribed ocular antibiotic drops without eye patching, and then patients were re-assessed two days after the procedure.…”
Section: Discussionmentioning
confidence: 94%
“…Segal et al 6 found oxygen use during transport and recovery to be a significant risk factor, supporting the idea that face masks are a preventable cause of abrasions. Eye shields are commonly used during periorbital surgery to protect the eye from direct trauma; however, these must be inspected for surface irregularities before each case and require careful placement/removal, as they have been known to cause corneal injury.…”
Section: Preventionmentioning
confidence: 84%
“…3,6,15 Longer anesthesia times lengthen the period of diminished protective mechanisms. Furthermore, tear production 16 and breakup time 4 are reduced to an even greater extent with increasing duration of general anesthesia.…”
Section: Perioperative Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Published data report an incidence range of 0.17%-44%. 7 Roth S et al studied-on eye injuries during anaesthesia in a huge number of patients and concluded that lengthier the procedures more the eye injuries. 2 Most corneal abrasions are not due to trauma alone but instead due to drying of corneal epithelium probably due to the decreased basal tear production.…”
Section: Introductionmentioning
confidence: 99%